2022
DOI: 10.3389/fendo.2022.1001728
|View full text |Cite
|
Sign up to set email alerts
|

Repeat thyroid FNAC: Inter-observer agreement among high- and low-volume centers in Naples metropolitan area and correlation with the EU-TIRADS

Abstract: Our institution (University Hospital "L. Vanvitelli" -Naples, Italy) is a highvolume (HV) center in Naples metropolitan area and many patients are referred there to repeat thyroid fine-needle aspiration cytology (FNAC) after initial FNAC performed in low-volume institutions (LV). The aims of the study were to 1) examine the inter-observer agreement between HV and LV institutions according to the Italian thyroid cytology system, and 2) explore how the discordant FNAC reports were distributed in the European Thy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…This cohort finally included 309 nodules with PTC histology having a mean md of 14 ± 7.8 mm, about two-thirds with md ≥ 10 mm. According to current evidence [ 17 , 32 ], our nodules mainly distributed in high risk TI-RADS categories (i.e., over 95% were TR5 and TR4, and less than 5% were TR3). Overall, we found that the cytology exam overestimated the percentage of classical PTC cases while it underestimated the percentage of non-classical PTC cases: indeed, histology of PTC subtypes revealed about 10% less of classical PTC and about 10% more of non-classical PTC cases compared to cytology.…”
Section: Discussionmentioning
confidence: 95%
“…This cohort finally included 309 nodules with PTC histology having a mean md of 14 ± 7.8 mm, about two-thirds with md ≥ 10 mm. According to current evidence [ 17 , 32 ], our nodules mainly distributed in high risk TI-RADS categories (i.e., over 95% were TR5 and TR4, and less than 5% were TR3). Overall, we found that the cytology exam overestimated the percentage of classical PTC cases while it underestimated the percentage of non-classical PTC cases: indeed, histology of PTC subtypes revealed about 10% less of classical PTC and about 10% more of non-classical PTC cases compared to cytology.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, it is relatively safe, repeatable, and low risk [6,7,9,10]. However, CS can report variable results, depending on the uneven thyroid tissue samples or cytopathologist's experience [8,10,11]. Artifacts may also arise during the drying of specimens, and results can vary by technician [9].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, a second FNA of the same nodule could help the pathologist make a more precise diagnosis. The experience of cytopathologists, added to the collaboration with clinicians, leads to better classification of thyroid nodules [ 11 ].…”
Section: Introductionmentioning
confidence: 99%